Why Do Males Use Multiple Signals? Insights From Measuring Wild Male Behavior Over Lifespans - Deodhar, Shreekant; Isvaran, Kavita (Frontiers in Ecology and Evolution, 2018)
Why animals commonly use multiple conspicuous and presumably costly signals is poorly understood. Tests of evolutionary hypotheses comprehensively covering the signaling repertoire in wild populations are crucial to establish biological relevance, yet are relatively rare. We tested a key hypothesis for the maintenance of multiple signals in a wild population of the lizard, Psammophilus dorsalis, specifically whether multiple signals are maintained as multiple messages directed at different receivers. In addition, we also examined patterns in covariation of signals as an initial test of an alternative hypothesis, that multiple signals may be maintained as redundant signals; such traits are proposed to convey and reinforce the same component of information and are expected to be strongly correlated. Breeding male P. dorsalis display from prominent rock perches within their territories, which overlap multiple female home ranges in rocky open habitats. We repeatedly measured the display behavior, covering the entire signaling repertoire, of individually-tagged wild males on their territories over their lifespans. We quantified patterns of covariation in multiple traits and their relationship with multiple receiver contexts, specifically competitors, mates and predators. We also examined the association between male signaling and indices of lifetime fitness. Males commonly used multiple signals, including behavioral signals and a rare dynamic color signal. These traits were strongly correlated and seemed largely directed toward females, suggesting that they were primarily maintained as redundant signals through female choice. However, other selection pressures also appeared to be important. One color trait seemed to be directed at competitors, providing limited support to the multiple receiver hypothesis. Several traits were reduced in the presence of predators, suggesting that they carry the cost of increased predation risk. Thus, multiple selection pressures, primarily female choice and predation risk, appear to affect male signaling. Finally, signaling traits appeared to influence a measure of lifetime reproductive success, providing rare evidence for the biological relevance of signaling traits under natural contexts.